Internalisasi Nilai-Nilai Pancasila Dalam Pembentukan Karakter Mahasiswa Di Era Digital - Aprianto (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the process of internalizing Pancasila values in shaping student character in the digital era. Using a qualitative approach and case study method at several universities in Indonesia, the research explores how Pancasila values are understood, experienced, and practiced by students in both academic settings and daily life. The findings reveal that the internalization process is more effective when carried out through participatory, contextual, and experience-based approaches. Additionally, digital technology holds great potential to support this process, provided that it is accompanied by digital literacy and appropriate pedagogical strategies. The main challenges include the lack of integration of Pancasila values into all aspects of campus life and the negative influence of digital content that contradicts national values. Therefore, the role of lecturers, campus environment, and wise use of technology are key to successfully forming student character grounded in the noble values of Pancasila.